Improved biocompatibility and efficient labeling of neural stem cells with poly(L-lysine)-coated maghemite nanoparticles - Pongrac, Igor M.; Dobrivojević, Marina; Ahmed, Lada Brkić; Babič, Michal; Šlouf, Miroslav; Horák, Daniel; Gajović, Srećko (Beilstein Journal of Nanotechnology, 2016)
Background: Cell tracking is a powerful tool to understand cellular migration, dynamics, homing and function of stem cell transplants. Nanoparticles represent possible stem cell tracers, but they differ in cellular uptake and side effects. Their properties can be modified by coating with different biocompatible polymers. To test if a coating polymer, poly(L-lysine), can improve the biocompatibility of nanoparticles applied to neural stem cells, poly(L-lysine)-coated maghemite nanoparticles were prepared and characterized. We evaluated their cellular uptake, the mechanism of internalization, cytotoxicity, viability and proliferation of neural stem cells, and compared them to the commercially available dextran-coated nanomag®-D-spio nanoparticles.Results: Light microscopy of Prussian blue staining revealed a concentration-dependent intracellular uptake of iron oxide in neural stem cells. The methyl thiazolyl tetrazolium assay and the calcein acetoxymethyl ester/propidium iodide assay demonstrated that poly(L-lysine)-coated maghemite nanoparticles scored better than nanomag®-D-spio in cell labeling efficiency, viability and proliferation of neural stem cells. Cytochalasine D blocked the cellular uptake of nanoparticles indicating an actin-dependent process, such as macropinocytosis, to be the internalization mechanism for both nanoparticle types. Finally, immunocytochemistry analysis of neural stem cells after treatment with poly(L-lysine)-coated maghemite and nanomag®-D-spio nanoparticles showed that they preserve their identity as neural stem cells and their potential to differentiate into all three major neural cell types (neurons, astrocytes and oligodendrocytes).Conclusion: Improved biocompatibility and efficient cell labeling makes poly(L-lysine)-coated maghemite nanoparticles appropriate candidates for future neural stem cell in vivo tracking studies.
Keywords: dextran; maghemite; nanoparticles; neural stem cells; poly(L-lysine)